2014
DOI: 10.5539/ies.v7n3p99
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of L1 Phonemic Awareness into L2 Reading: The Case of Arab EFL Readers

Abstract: Cross-language transfer is the extent, if any, to which phonological awareness in L1 facilitates learning to read in L2. This has been an area of investigation wherein researchers looked into the orthographic and phonological component processing skills L2 learners develop and utilize to facilitate word recognition. Given the difference between the orthographic systems of Arabic (L1) and English (L2), how difficult is it for beginning Arab EFL learners to develop these skills? Arab EFL learners seem to have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
(40 reference statements)
1
2
0
1
Order By: Relevance
“…Generally, the results of the current study supports the theory that beginning Arabic readers must map orthographic information to corresponding phonological information to identify a word (Elbeheri et al, 2011;Asadi et al, 2017b). Arabic orthography could be defined as phonologically transparent where the grapheme represents the same phoneme or the phoneme represents the same grapheme consistently (Alshaboul et al, 2014).…”
Section: Morphological Processingsupporting
confidence: 83%
“…Generally, the results of the current study supports the theory that beginning Arabic readers must map orthographic information to corresponding phonological information to identify a word (Elbeheri et al, 2011;Asadi et al, 2017b). Arabic orthography could be defined as phonologically transparent where the grapheme represents the same phoneme or the phoneme represents the same grapheme consistently (Alshaboul et al, 2014).…”
Section: Morphological Processingsupporting
confidence: 83%
“…For example, phonological awareness in Arabic was correlated to phonological awareness in English (Farran et al, 2012). Similarly, a study conducted by Alshaboul et al (2014) found evidence of transfer of phonological awareness from Arabic to English in first-grade Jordanian bilingual children aged 6 to 10. These findings confirm that phonological skills are an important factor in the development of basic literacy skills within and across languages, as phonology is primary to reading in most languages (Share, 1995) or is accessed as early as permitted by the writing system (Perfetti et al, 2005).…”
Section: Phonological Awarenessmentioning
confidence: 82%
“…L'identification des mots écrits et l'épellation en L2 sont alors souvent de même niveau que chez des enfants L1 (Geva, 2009). Une bonne conscience phonologique en L1 se répercuterait également positivement sur la lecture en L2, par transfert inter-linguistique (Alshaboul et al, 2014). Alors que Geva et son équipe étudient des groupes bilingues hétéroclites, le bilinguisme au Liban offre un contexte plus homogène, propice à l'étude de l'apprentissage de l'écrit et à la détection de pathologies en lecture en cas de bilinguisme.…”
Section: Bilinguisme Et Apprentissage De La Lecture Au Libanunclassified